2022
DOI: 10.7759/cureus.26505
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Cardiac Arrest Outcomes in the United States: A Nationwide Database Cohort Study

Abstract: BackgroundKnowledge about the causes and outcomes of pediatric cardiac arrest in the emergency department is limited. The aim of our study was to evaluate the characteristics and outcomes of pediatric cardiac arrest in the emergency department (EDCA) and inpatient (IPCA) settings in the United States using a large database designed to provide nationwide estimates. MethodsWe performed a retrospective cohort study using the Nationwide Emergency Department Sample (NEDS), a database that includes both ED and inpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…The incidence rates, common causes, and demographic considerations of pediatric cardiac arrest are essential factors in understanding the epidemiology of this critical condition. The overall incidence rate for out-of-hospital cardiac arrest (OHCA) in the United States is 8.3 per 100,000 person-years, with a survival to hospital discharge rate of 11.3% [ 6 ]. Pediatric OHCA rates are reported to be 6-10 per 100,000 person-years, with only about 10% of patients surviving hospital discharge [ 7 ].…”
Section: Reviewmentioning
confidence: 99%
“…The incidence rates, common causes, and demographic considerations of pediatric cardiac arrest are essential factors in understanding the epidemiology of this critical condition. The overall incidence rate for out-of-hospital cardiac arrest (OHCA) in the United States is 8.3 per 100,000 person-years, with a survival to hospital discharge rate of 11.3% [ 6 ]. Pediatric OHCA rates are reported to be 6-10 per 100,000 person-years, with only about 10% of patients surviving hospital discharge [ 7 ].…”
Section: Reviewmentioning
confidence: 99%
“…The mortality rate of pediatric In Hospital Cardiac Arrest (IHCA) is high and the survival rates were reported as 41.1% compared to 11.4% for Out-Hospital Cardiac Arrest (OHCA). Also, the survival rates of IHCA differs among departments and cardiac arrest in the emergency department has higher mortality than Inpatient Cardiac Arrest (IPCA) (1). Mckenzie et al found that a high proportion of pediatric OHCA had ROSC (Return of spontaneous circulation), but the rate of survival to discharge was low (2).…”
Section: Introductionmentioning
confidence: 99%